Annual Plan 1995-96 Volume-XI Hill Areas Government of Assam - Planning Commission (Planning Commission, 1995)
The Health plan proposals aim at providing curative, preventive, promotive, maternity and child health Nutrition and Family Planning services, the plan aims at giving sufficient medical coverage in-rural and backward areas.
Government of Assam, Development Commissioner for Hill Areas